Impact of polysaccharide and protein interactions on membrane fouling: Particle deposition and layer formation - Zhang, Chao; Bao, Qi; Wu, Huanan; Shao, Mingshuai; Wang, Xue; Xu, Qiyong (Chemosphere (Oxford), 2022)
Membrane fouling, which limits the application of membrane bioreactors, has received considerable research attention in recent years. In this work, filtration modeling was performed in combination with surface plasmon resonance (SPR) analysis to investigate the membrane fouling mechanism. Sodium alginate (SA) and bovine serum albumin (BSA) were used to perform dead-end filtration on hydrophilic and hydrophobic poly (vinylidene fluoride) (PVDF) membranes. The initial foulant deposition and layer formation on membranes as well as the interaction between the BSA and SA were comprehensively analyzed. Results indicated that during SA filtration, initial fouling on hydrophilic membranes were primarily attributed to the particle–membrane interactions, while the fouling on the hydrophobic membrane were dominantly caused by the interactions among SA particles. The interaction between BSA and SA led to more severe membrane fouling and hydrophobic membrane was more sensitive to it, especially in the initial filtration process. The SPR results helped clarify the in-situ deposition behavior of BSA and SA particles on the PVDF surface. Compared to SA, BSA adsorbed faster on the PVDF membrane, and specific interactions played an essential role in BSA adsorption, whereas the deposition of SA on PVDF could be easily removed by shear force. Interactions between BSA and SA could alleviate the bonding between BSA and the PVDF membrane. [Display omitted] •Specific interaction plays an important role in BSA adsorption.•BSA generates faster fouling than SA on the hydrophobic membrane.•Interactions between BSA and SA alleviate complete blockage.•Interactions between BSA and SA eliminated the bonding between BSA and membrane.